Buddhism and Beyond: The Question of Pluralism - Duckworth, Douglas S. (Interreligious studies and intercultural theology, 2020)
This article discusses Buddhist responses to religious diversity. I use the logical form of the tetralemma made famous by Nāgārjuna to clarify the ways that Buddhists can be seen to relate to other religions. With four alternatives, I discuss Buddhist claims to truth in terms of their being singularly absolute, one among many, both, and neither. As is evident in the presence of the third and fourth alternatives of the tetralemma, rigid dichotomies (like one and many, exclusivism and pluralism) are often false, for both (and neither) are live options. A key difference rests on the interpretation of ultimate truth, and in particular, whether the ultimate truth of emptiness is interpreted as a claim to the indeterminate nature of reality or its undetermined nature. The undetermined involves a participatory attitude of openness, and a healthy suspicion of preconceptions that determine and delimit the ultimate truth. Thus, the undetermined refers not so much to a descriptive truth, but rather to how one comports oneself in the world - with humility and openness. In parallel with this distinction between openness and certainty, I also spell out differences between claims and attitudes in an example from Tibetan traditions, with reference to the so-called "nonsectarian" (ris med) movement in particular. I argue that the difference between claims and attitudes can help clarify what it means to be "nonsectarian," and thereby bridge the difference between maintaining an exclusively Buddhist claim and having an attitude that reaches beyond Buddhism.